Produção e caracterização física de carvões ativados a partir de fibras de piaçava pré-tratadas - Castro, Jonnys Paz (2016)
Studies aimed at obtain adsorbents for pollutants removal from the aqueous medium are increasing, and the activated carbon is the main adsorbents investigated. Thus, alternative sources for obtaining CAs also become important focus of research. Piassava fibers have great economic importance in Brazil and, during its production and processing, large amount of residues are generated. These residues have great potential to be use as feedstock to ACs preparation. The piassava fibers have smooth and impermeable texture and this may influence the properties of the activated carbon, so that use of pretreatments may enhance the physical properties and adsorption capacity of the activated carbons produced. Thus, the scope of the present work was to evaluate the effect of different pretreatments on the Amazon piassava fiber (Leopoldinia piassaba) and Bahia piassava fiber (Attalea funifera Martius) and on the properties of activated carbons obtained from those fibers. Three pretreatment were evaluated: Corona (electrical discharge), mercerization (NaOH) and extractive-free (solvent). Analyses to evaluate the adsorption capacity and other properties and characteristics of activated carbons were realized. This thesis was divided into two parts. The first part consists of state of the art on the piassava fibers and on some topics covering activated carbons. The second features three different papers. The first paper corresponds to the production and characterization of activated carbons (physically activated with CO2) from Amazon piassava fibers untreated and pretreated, using three different processes. The second article includes information about the influence of pretreatments in the production of activated carbons (physically activated with CO2) from Amazon and Bahia piassava fibers untreated and pretreated. The third article covers studies involving the adsorption capacity of methylene blue, iodine, chromium (VI) and 2,4-D by different activated carbons obtained from Amazon and Bahia piassava fibers pretreated and untreated. In this case three different activation processes (physical using CO2 or H2O vapor and chemical using KOH) were used. The pretreatments influenced the properties of the activated carbons produced, highlighting the treatment that consist in remove the extractives of the piassava fiber. The ACs obtained from Amazon piassava fibers showed better results compared to ACs obtained from Bahia piassava fibers. In adsorptions of methylene blue, iodine and 2,4 D, the carbons chemically activated with KOH were more effective. ACs prepared from Amazon and Bahia piassava fibers by physical (CO2 and H2O vapor) and chemical (KOH) activations showed great potential for use as adsorbent.